Integrating project-based learning with authentic news video production: A qualitative case study on news text literacy development in Indonesia's Merdeka Curriculum - Noveria, Ena; Ulya, Ridha Hasnul; Radi Sukma; Tressyalina (Universitas Ahmad Dahlan, 2026)
Conventional news text instruction often neglects oral communicative competence, prioritizing written analysis over speaking performance. This study investigates the effectiveness of integrating Project-Based Learning (PjBL) with authentic news video production to enhance seventh-grade students' speaking skills within the Merdeka Curriculum. Employing a qualitative case study design, data were collected through methodological triangulation comprising limited participatory observation, semi-structured in-depth interviews, supportive questionnaires, and documentary analysis of student scripts and video products within a coastal-region SMP. Analysis followed Miles, Huberman, and Saldaña's interactive model through iterative cycles of data reduction, display, and conclusion verification. Findings revealed that 70 percent of students demonstrated enhanced comprehension of news text structure through functional internalization of 5W+1H elements and the inverted pyramid principle during rigorous scriptwriting. Learning motivation increased by 65 percent, attributed to the authentic experience of